The Peruvian Administrative Process: Brief history, present and future perspectives - Jiménez Vivas, Javier Eduardo (2020)
The article presents a brief history of the Peruvian administrative process, from the 19th century to the 21st century, both in the normative (constitutional and legal), doctrinal and jurisprudential fields. It explains the scope of its constitutional recognition, its main principles and its most important concepts. It also explores itsfuture perspectives.